Effects of different conditions on growth of tomato plants infected with Meloidogyne javanica - Meon, Sariah (Malaysian Society of Applied Biology, 1980)
Infection of tomato plants by Meloidogyne javanica resulted in a decrease in the ratio of fresh weight of tops to roots. With increasing inoculum density there was a gradual increase in root weight due to increased number and size of galls produced. Temperature,moisture and nutrition had a significant effect on fresh weight of tops and number of females recovered from the infected roots. Under optimal growth conditions, top growth did not differ significantly